Sequential Pathological and Immunohistochemical Study of Pullorum Disease in Experimentally Infected Chicks - Shahinuzzaman, A.B.M.; Saha, A.K.; Mazumder, A.C.; Das, S.; Sufian, M.A.; Baki, M.A.; Hossain , M.M. (International Journal of Poultry Science, 2011)
The research work was conducted to study the sequential pathological changes of Pullorum Disease (PD) and immunohistochemical detection of its causal agent (Salmonella pullorum) in various tissues of experimentally infected chicks. Total 40 day old (D0) chicks were divided into experimental and control groups. The chicks were infected at day 15 (D15) of age by oral route with 1 ml of 2 x 108 CFU of S. pullorum. Chicks were sacrificed at day 1 (D1), day 3 (D3), day 5 (D5), day 7 (D7) and day 9 (D9) of Post Infection (PI) and observed the remarkable gross lesions in liver, lung, heart and cecum. Grossly, liver found fragile (40%) at D7 and D9. Cheesy materials in cecum (20%) showed at D9. The highest reisolation of S. pullorum demonstrated in cecum (68%). Histopathologically, nodular lesion in liver developed at D7 (20%) and D9 (40%). Hepatitis from D1 (20%) and continued upto D9 (60%). Pneumonia and bronchopneumonia along with inflammatory cells in lung were observed at D1 (20%) that continued upto D9 (80%). Spleen showed depletion of lymphocytes at D7 (40%) and D9 (60%). Typhlitis in cecum noticed at D5 (20%) and remained up to at D9 (40%). Congestion and hemorrhage was common in organs at early times and gradually reduced both in grossly and histopathologically thereafter. Immunohistochemistry revealed S. pullorum bacteria in the cytoplasm of hepatocytes of liver, in the cytoplasm of epithelia of cecum (D3, D7) and in the cytoplasm of epithelia of crop (D3).